2007
DOI: 10.1007/s10389-007-0144-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental noise exposure and population health: a cross-sectional study in the Province of Rome

Abstract: Background The aim of the present study is to analyse the relationship between exposure to environmental noise and population health-perceived status in a cross-sectional setting in Italy. Methods A cross-sectional study was carried out, in a population in the Province of Rome (Castelnuovo di Porto), in order to evaluate the auditory impact of road and railway infrastructures on population quality of life (QOL). Environmental noise due to road and railway traffic was assessed by phonometric samples during 1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…For the strengths, we considered a sample distributed in different Italian regions, to acquire knowledge and data before missing regarding quality of life in different categories of health care professionals [30][31][32]. Moreover, to avoid confounding we performed the multivariate analysis so the results were adjusted for possible confounders.…”
Section: Discussionmentioning
confidence: 99%
“…For the strengths, we considered a sample distributed in different Italian regions, to acquire knowledge and data before missing regarding quality of life in different categories of health care professionals [30][31][32]. Moreover, to avoid confounding we performed the multivariate analysis so the results were adjusted for possible confounders.…”
Section: Discussionmentioning
confidence: 99%
“…The European Directive 2002/49/EC lays emphasis on environmental noise and related problems and obligates the member states to provide access to the information on noise pollution 3 . Numerous noise mapping studies have been reported in different countries [4][5][6][7][8][9] . However, as of yet, no study has been reported on the time-series prediction of traffic noise levels.…”
Section: Introductionmentioning
confidence: 99%
“…Most important of these are annoyance (Michaud et al, 2005) and sleep disturbance (Carter, 1996;Ohrstrom and Skanberg, 2004). However, other dose-effect relationships include negative emotions such anger, disappointment, unhappiness, anxiety and even depression as well as mental health impacts (Fidell et al, 1991;Fields, 1998;Miedema, 2003;Michaud et al, 2005;La Torre et al, 2007). A further area of concern is the link between noise exposure and cardio-vascular disease (Babisch et al (2003(Babisch et al ( , 2005 while noise has a particularly negative impact on children's health (Evans and Lepore, 1993;Evans et al, 2001;Evans and Maxwell, 1997).…”
Section: Introductionmentioning
confidence: 99%